Examining The Attitudes of E-Sports Players Towards Artificial Intelligence Techologies - YORULMAZLAR, MEHMET MUSTAFA; ÇETİN, ARİF (My University, 2023)
This study aimed to examine the attitudes of e-sports participants toward artificial intelligence (AI) based on a variety of socio-demographic variables. A total of 206 e-sports participants selected through convenience sampling were administered the "Attitude Towards Artificial Intelligence Scale" adapted by Kaya et al. (2022). SPSS 29.0.1.0 (171) was used to analyse the data. For data analysis, the Whitney U and Kruskal Wallis tests were utilized. According to the results of the analysis, there was no significant difference in the age variable, whereas the gender variable produced results that favoured male e-sports participants. In addition, it was discovered that individuals who used technological devices during exercise more frequently had a more positive attitude towards AI. In conclusion, men participants have a more optimistic view of artificial intelligence than female participants. These results illustrate the connection between technology usage and perception of artificial intelligence. It can be hypothesized that individuals who frequently use technological devices during exercise are more conversant with technology and, as a result, have a more favourable attitude towards artificial intelligence. These results indicate that technology utilization influences the adoption and acceptance of AI technologies. Keywords: Artificial Intelligence, E-Sports, Technology and Sports
Keywords: Artificial Intelligence; E-Sports; Technology and Sports